A case of carcinoma of the papilla of Vater in a young man after subtotal colectomy for familial adenomatous polyposis. Issue 1 (December 2016) - Komori, Shuji; Kawai, Masahiko; Nitta, Toyoo; Murase, Yusuke; Matsumoto, Keita; Shinoda, Chika; Kuno, Masashi; Sasaguri, Yuki; Fukada, Masahiro; Asano, Yoshimi; Kiyama, Shigeru; Tanaka, Chihiro; et al.
Abstract Background Carcinoma and adenoma of the duodenum, including the papilla of Vater, are problematic diseases in patients with familial adenomatous polyposis (FAP). Case presentation A 36-year-old man underwent a periodic medical examination for early colon cancer originating from FAP for which laparoscopic-assisted subtotal colectomy with a J-shaped ileal pouch-rectal anastomosis was performed 3 years earlier. A tumor was detected at the papilla of Vater along with elevation of total bilirubin and hepatobiliary enzymes. Although cytology did not determine the tumor to be an adenocarcinoma, we suspected adenocarcinoma due to its hypervascularity shown by contrast-enhanced computed tomography. Pylorus-preserving pancreaticoduodenectomy with modified Imanaga reconstruction and regional lymph node dissection (D2) was performed. The pathological study showed that the tumor was a papillary and moderately differentiated tubular adenocarcinoma. The patient is currently in good health without recurrence, weight loss, or severe diarrhea at 12 months after surgery. Conclusions Awareness of biliary-pancreatic symptoms and periodic gastroduodenoscopy might contribute both to the early detection of duodenal or periampullary polyps and cancer and to the radical treatment of FAP. Modified Imanaga reconstruction has the potential to become one of the more effective procedures for providing good quality of life to FAP patients with duodenal or periampullary cancer.